Recent advances in transition metal based compound catalysts for water splitting from the perspective of crystal engineering. Issue 9 (16th December 2019) - Ju, Min; Wang, Xiaoting; Long, Xia; Yang, Shihe
Abstract : A review of the recent progress on the transition metal based catalysts for water splitting with emphasis on crystal engineering. Abstract : Although the study of energy storage and conversion by electrochemical and electrocatalytic strategies increasingly involves complex composites and heterostructures, it is known that the intrinsic properties of a particular crystalline material can also greatly affect its catalytic performance. Crystal engineering strategies involving the target morphology, specific crystal phase and orientation, as well as the local atomic structure have proven to be promising for future batteries, supercapacitors or electrocatalysts. In this perspective, we summarized the recent progress in crystal engineering of transition metal based electrocatalysts for efficient hydrogen generation via water splitting.